A comparison of ICD-11 and DSM-5 criteria of PTSD among Chinese trauma-exposed adolescent samples - Wang, Li; Fang, Ruojiao; Chen, Chen; Cao, Chengqi (Frontiers in Psychiatry, 2023)
This study aimed at comparing the prevalence and comorbidity differences of PTSD according to ICD-11 and DSM-5 definitions across two Chinese adolescent trauma-exposed samples. A total of 1,201 students exposed to earthquake and 559 students from vocational schools exposed to potentially traumatic events were included in this study. The PTSD Checklist for DSM-5 was used to measure PTSD symptoms. The MDD and GAD subscales of the Revised Children’s Anxiety and Depression Scale were used to measure major depression disorder (MDD) and generalized anxiety disorder (GAD) symptoms. No significant PTSD prevalence differences between ICD-11 and DSM-5 were found across the two samples. The differences regarding comorbidities between ICD-11 and DSM-5 definitions were not significant among these two samples. The results revealed that the ICD-11 and DSM-5 provided similar prevalence of PTSD and comorbidity rates with MDD and GAD in Chinese trauma-exposed adolescent samples. This study contributes to the current understanding of the similarities and differences using different PTSD criteria and informs the organization and application of these two globally applied PTSD criteria.